Verbal behavior: from Chomsky’s criticisms to contemporary developments in language understanding - Schmidt, Andreia; Cortez, Mariéle Diniz (Perspectivas em Análise do Comportamento, 2025)
The chapter “Verbal Behavior” from the book About Behaviorism was published 17 years after the release of Verbal Behavior. During that interval, considerable debate emerged regarding the value of Skinner’s propositions on the topic, including the widely known criticisms by Chomsky. The present study aimed, based on the content of this chapter, to present and discuss the main developments arising from Skinner’s formulation for the study and understanding of verbal behavior. In this chapter, Skinner reaffirms key elements of his approach: the concept of meaning as a product of reinforcement contingencies, the rejection of mentalistic explanations, and the functional distinctions between speaker and listener behaviors. Behavior-analytic perspectives developed in subsequent decades — such as Bidirectional Naming (BiN), the stimulus equivalence paradigm, and Relational Frame Theory (RFT) — have expanded the empirical and conceptual foundations regarding meaning, reference, symbolic functions, and derived relational responding. Recent efforts to integrate BiN, the stimulus equivalence paradigm, RFT, and the Skinnerian analysis seek to provide a more comprehensive understanding of the processes involved in verbal behavior. This article reaffirms that, despite early criticisms, Skinner’s proposal remains vital and relevant, continuing to support both research and educational programs.